Nitrogen and potassium application by fertigation at different watermelon planting densities - Cecílio Filho, L. A B [UNESP]; Feltrim, A. L. [UNESP]; Mendoza Cortez, J. W. [UNESP]; Gonsalves, M. V. [UNESP]; Pavani, L. C. [UNESP]; Barbosa, J. C. [UNESP] (Springer Nature, 2015)
The effects on the production of ‘Top Gun’ watermelons were evaluated at N and K (N+K2O) doses via fertigation of 79.8+106.7, 106.4+142.2, 133.0+177.7, and 159.6+213.2 kg ha-1 and at plant spacings of 0.5, 1.0, 1.5, and 2.0 m. The experiment had a split-plot randomised block design with three replicates. N+K2O doses and plant spacings were randomised in the plots and subplots, respectively. We evaluated foliar N and K contents, average mass of commercial fruits (MF), total (FT) and commercial (FC) number of fruits, and total (PT) and commercial (PC) productivity of weight classes 6-8, 8-10, 10-12, and >12 kg per area and plant. The N+K2O doses only influenced the foliar K content. The other variables were not influenced by the interaction of factors or by the N+K2O doses. Plant spacing influenced fruit number and production. Reducing plant spacing from 2.0 to 0.5 m decreased MF, FT, FC, PT, and PC of the classes per plant but increased FT, FC, PT, and PC of the 6-8 and 8-10 kg classes per area.
Keywords: Citrullus lanatus; Mineral nutrition; Plant spacing